2021
DOI: 10.1007/s11686-021-00340-4
|View full text |Cite
|
Sign up to set email alerts
|

The Neglected Role of Trichomonas tenax in Oral Diseases: A Systematic Review and Meta-analysis

Abstract: Purpose: Trichomonas tenax (T. tenax) is a commensal flagellated protozoan found in periodontal microenvironment of the oral cavity, with a possible role in periodontal diseases. The purpose of the present systematic review and meta-analysis was to determine the worldwide prevalence of T. tenax infection and to show the neglected association of this parasitic infection with oral diseases. Methods: To find literatures published until August 2020, five English databases (PubMed, Scopus, Science Direct, Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…In periodontitis, the role of the bacterial fraction of the oral microbiome has been studied extensively with accumulating evidence pointing to its contribution to the etiology of the disease ( Teles et al., 2013 ). However, the fraction of protozoa was not studied to a similar level compared to its bacterial counterpart ( Deng et al., 2017 ; Bonner et al., 2018 ; Bisson et al., 2019 ; Santi-Rocca, 2020 ; Badri et al., 2021 ; Eslahi et al., 2021 ). Nevertheless, this protozoan fraction does not seem to be negligible in some clinical setups, with E. gingivalis RNA accounting for up to 9% of the total RNA in periodontal pockets ( Deng et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In periodontitis, the role of the bacterial fraction of the oral microbiome has been studied extensively with accumulating evidence pointing to its contribution to the etiology of the disease ( Teles et al., 2013 ). However, the fraction of protozoa was not studied to a similar level compared to its bacterial counterpart ( Deng et al., 2017 ; Bonner et al., 2018 ; Bisson et al., 2019 ; Santi-Rocca, 2020 ; Badri et al., 2021 ; Eslahi et al., 2021 ). Nevertheless, this protozoan fraction does not seem to be negligible in some clinical setups, with E. gingivalis RNA accounting for up to 9% of the total RNA in periodontal pockets ( Deng et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For T. tenax , the estimates were much lower and significant differences were found moving from 3.2% in the healthy group to 18.2% among individuals with periodontal disease. To assess the reproducibility of these results, a limited number of studies were found ( Kikuta et al., 1996 ; Trim et al., 2011 ; Bonner et al., 2014 ; Garcia et al., 2018a ; Santi-Rocca, 2020 ; Badri et al., 2021 ; Eslahi et al., 2021 ). The comparisons were further complicated by the reliance of a majority of the previous studies on microscopic detection methods (examination of wet mounts or permanent stained smears) ( Athari et al., 2007 ; Ghabanchi et al., 2010 ; Al-hamiary et al., 2011 ; Ibrahim and Abbas, 2012 ; Yazar et al., 2016 ; Hassan et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amoeba has been found scavenging in the healthy oral cavity, but there are still discrepancies regarding the true effect of the E. gingivalis on the hygienic status of the oral cavity (7,8). Some researchers suggest that this organism provokes periodontitis, while others remark that the protozoan is only an opportunistic survivor in the molecular milieu elicited by periodontal disease (9)(10)(11). However, it is recognized that E. gingivalis acts synergistically with symbiotic bacteria to cause periodontal disease in immunocompromised hosts (12).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, T. tenax has also been detected in other tissues and organs of the body such as the respiratory tract and lymph nodes [ 6 , 7 , 8 , 9 ]. T. tenax has been reported in humans since the 1960s [ 4 ] and has been specifically connected to human periodontal disease by a systematic review and meta-analysis of 65 qualified publications [ 10 ]. In a prospective study carried out in Jordan recently, it has been found that the prevalence of T. tenax among healthy, gingivitis and periodontitis groups is 3.2%, 5.7% and 25.6%, respectively.…”
Section: Introductionmentioning
confidence: 99%